PEMANFAATAN MEDIA SOSIAL INSTAGRAM @INFOBMKG SEBAGAI MEDIA PUBLIKASI EDUKASI SIKLON TROPIS DALAM UPAYA MENGANTISIPASI MISINFORMASI - Larasati, Razita; Muljono, Pudji; Fuad Cholagi, Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of social media encourages government institutions to utilize it as a public education tool, particularly in disaster contexts prone to misinformation. This study aims to analyze the use of Instagram @infobmkg as a medium for tropical cyclone education and its communication effects. This research employs a qualitative case study approach using interviews, observations, and documentation. The results show that social media management based on context, communication, collaboration, and connection has been implemented optimally. Furthermore, the educational content generates cognitive, affective, and behavioral effects, including increased understanding, emotional reassurance, and behavioral changes in filtering and sharing information. It is concluded that Instagram @infobmkg is effective as an educational medium to anticipate disaster-related misinformation.